2010
DOI: 10.1007/s00270-010-9971-2
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Assisted Coil Embolization of a Mycotic Renal Artery Aneurysm by Use of a Self-Expanding Neurointerventional Stent

Abstract: Mycotic aneurysms are uncommon, especially those located in visceral arteries. We present a case of a patient with two visceral mycotic aneurysms due to bacterial endocarditis, one located in right upper pole renal artery and the second in the splenic artery. Both aneurysms were treated as endovascular embolization using microcoils. In the aneurysm located at the renal artery, the technique of stent-assisted coils embolization was preferred to avoid coils migration due to its wide neck. The stent used was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…10 Moreover, several cases of celiac, hepatic, splenic, or renal mycotic aneurysm successfully treated by endovascular therapy have been reported. 1113 A past report suggested that unruptured mycotic aneurysm could be adequately managed by first initiating long-term antibiotics, followed by endovascular therapy to minimize recurrent infection. 14 Our patients underwent long-term antibiotic therapy before TAE was performed because mycotic aneurysms were initially detected on CT around 4 weeks after diagnosis of infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, several cases of celiac, hepatic, splenic, or renal mycotic aneurysm successfully treated by endovascular therapy have been reported. 1113 A past report suggested that unruptured mycotic aneurysm could be adequately managed by first initiating long-term antibiotics, followed by endovascular therapy to minimize recurrent infection. 14 Our patients underwent long-term antibiotic therapy before TAE was performed because mycotic aneurysms were initially detected on CT around 4 weeks after diagnosis of infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…SAE as a therapeutic choice for RAA has been previously reported. 17,18 Similar to intracranial aneurysms, SAE was also the preferred treatment for aneurysms with a wide base and located in branch artery. 14,19 However, as a result of the low morbidity of RAA, the treatment indication and effect of SAE on RAA remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Low cross-sectional-shaped coils are applied to occlude cerebral arteriovenous malformations and arteriovenous fistulas, but can also be indicated in tortuous peripheral vasculature, as diagnostic catheters may not be navigated to the target vessels and microcatheters are the preferred delivering catheter. 38 , 39 …”
Section: Metal Occlusion Devicesmentioning
confidence: 99%